Vulnerabilidad de la población adulta mayor del Cantón Latacunga para identificar un modelo de desarrollo local - Granja Robayo, Carlos Iván (2020)
The elderly population constitutes an important population group in the country and in the same way, despite international guidelines, the necessary attention has not been possible. The research was focused on analyzing the situation of vulnerability of the elderly to identify a local development strategy that allows the improvement of the quality of life of this priority group in Latacunga. The research report is used a qualitative-quantitative approach, with a descriptive methodology through the application of a survey validated by experts to 374 older adults in Latacunga; based on this, it was concluded that the people who care for the elderly are not fully trained for this. The elderly does not have access to specialized care centers and the physical activity field has been neglected. Recreational activities as part of a development strategy allow motivating active participation in this area, the promotion of the strategy in different institutions is intended to establish as a strategy.